Buenas prácticas de postcosecha en el cultivo de cacao (Theobroma cacao) - López Dicao, Carlos Manuel (2024)
This degree work focuses on good post-harvest practices in cocoa cultivation to describe the most effective methods to ensure the quality of raw materials for the production of cocoa products. The study used a non-experimental bibliographic approach, analyzing current literature and research articles related to the topic. The results obtained highlight fermentation as a key step to determine the final quality of the cocoa. In particular, fermentation in wooden boxes is considered the most effective technique to control the process and ensure a homogeneous grain. Drying is another important process and sun drying on raised beds has been shown to be very effective in maintaining the integrity and quality of cocoa beans. This method ensures optimal air circulation around the cocoa beans, reducing humidity evenly. However, mechanical drying is also an effective alternative, especially in adverse weather conditions or when speed in the process is required. In addition, the importance of proper storage of cocoa was emphasized, since improper handling can cause loss of quality, affecting the desired flavor and aroma. The combination of fermentation in wooden boxes and then sun drying in raised beds gives the best results in cocoa quality. This approach not only optimizes flavor and aroma, but also reduces post-harvest losses and promotes sustainable cocoa production practices.